Tandem synthesis of glycidol via transesterification of glycerol with DMC over Ba-mixed metal oxide catalysts - Kondawar, S. E.; Patil, C. R.; Rode, C. V. (ACS Sustainable Chemistry & Engineering, 2017)
Glycerol carbonate (GC) and glycidol (GD) are commercial products possible from glycerol transformation, which has become a subject of great importance. Among several basic catalysts screened in this work, BaO showed the highest glycerol conversion of 71% with almost complete selectivity to GC. A tandem synthesis of GD with a selectivity as high as 80% with 98% glycerol conversion could be achieved with mixed oxides of Ba and lanthanides (La and Ce) prepared by the coprecipitation method. Although BaO alone showed the highest basicity as measured by CO2 TPD, tuning of basicity by incorporation of CeO2 resulted in the formation of GD. Incorporation of Ba into the ceria matrix induced oxygen vacancies in the cerium oxide material. The presence of u"/v" doublets at 888.7 and 903.2 eV, respectively, in XPS of the Ba-Ce sample also confirmed the oxygen vacancies in the lattice. In this tandem approach to GD, the subsequent decarboxylation of initially formed GC was due to the presence of a CeO2 lattice with defects, which is known to be the best for CO2 adsorption. Increase in both catalyst loading and temperature showed a dramatic enhancement in GD selectivity. A plausible reaction pathway for the transesterification of glycerol with DMC to give GC followed by its decarboxylation to GD is also proposed based on the structural characterization and activity studies.

Two-phase system for the clean and high yield synthesis of furylmethane derivatives over- SO3H functionalized ionic liquids - Shinde, S. H.; Rode, C. V. (Green Chemistry, 2017)
A new and effective unique two-phase reaction system is investigated for the high yield production of tri(furyl) methane from furfural and furan. This strategy includes the use of an acidic aqueous phase (water + -SO3H functionalized IL) and furan phase, which significantly suppresses polymer formation, thereby increasing the yield of tri(furyl) methane. Furan serves as a reactant as well as an extraction solvent for the recovery of the condensation products. For comparison, different -SO3H functionalized ionic liquids are prepared and their performances evaluated for the condensation of furan and furfural. The ionic liquids with alkyl chain linkers are found to be more effective and acidic than those with imidazolium linked N-sulfonic acids. In addition, an increase in carbon chain length between imidazole/tri-ethylamine/pyridine and -SO3H, increases the catalytic activity of the respective ionic liquids. Among the several prepared ionic liquids, the strongly acidic imidazolium based butylsulfonic acid 6 shows the best activity with a maximum condensation product yield of 84%. This strategy offers a significantly high yield of the condensation products of furan and furfural compared to the traditional mineral acid route. The activity and stability of the -SO3H functionalized 6 is confirmed from seven successful recycles, in which there is no reduction in its activity. Finally, this new strategy is successfully extended for the condensation of furan derivatives (e. g. furan and 2-methylfuran) with several different aldehydes, ketones and alcohols.